COMPARISON OF COST AND TIME OF FLOOR SLAB WORKS ON CONVENTIONAL AND BUBBLE DECK SLAB METHODS - Rayhan Mahesa Kurnia; Azaria Andreas; Nuryani Tinumbia (Jurnal Infrastruktur, 2022)
Floor slab is one of the most important structure members in a building and one of the largest members consuming concrete. Conventional floor slab has been used for years and has disadvantages that can be improved with alternate methods. There is lot of alternative methods that have been used in the construction world such as precast slab, half precast, hollow core slab, and many more. One of the alternative methods is bubble deck slab. The spherical hollow reinforced concrete slab has been patented named Bubble Deck Slab is a method that removes concrete from the center part of a slab which doesn't do any structure functional, so it can reduce the dead load significantly. High-density polyethylene hollow sphere is used to replace the ineffective part of the slab, so it reduces the dead load and increases efficiency. With the HDPE ball substitution, there will be differences in cost and time compared to the conventional method. This research is taking the case research in Central Control Building of Power Plant Muara Tawar Project with quantitative method approach. The analysis is calculating the budget plan and scheduling with Microsoft Project. After the analysis, there is differences in cost and time between the methods. The bubble deck slab method has the advantages which have the cheaper cost of IDR. 142,128,506.44 or 14,442% and 1 day or 3,846% faster compared to the conventional. Even so, the conventional method is still the first choice because the very common methods in Indonesia and the ease of execution.